STUDI PERILAKU HARIAN KUKANG KALIMANTAN (Nycticebus menagensis) DI PUSAT REHABILITASI SATWA INTERNASIONAL ANIMAL RESCUE INDONESIA (IARI) KABUPATEN KETAPANG, KALIMANTAN BARAT - Daniati, Eva; Rifanjani, Slamet; Winarti, Indah (Universitas Tanjungpura, 2017)
The study aims to determine the daily behavior and characteristics of slow loris to assess their readiness to be released back into the wild after going through the rehabilitation phase. The results are expected to help design a more appropriate program of rehabilitation and conservation for the slow loris. Loris’s daily behavior observations were performed using focal animal sampling (Altmann, 1974). Observations were made at a distance of 1-2 meters from the cage. In accordance uptime slow loris an observation conducted from 18:00 pm until 6:00 pm, with write down the frequency behavior based on the duration of the specified time interval every 5 minutes. On average presentation behavior of slow loris that are stable, habituation there is a presentation of the total of displaced (37.77%), forage (30.68%), browse (15.65%), eat (9.71%), active (3.66%) and a low of behavior social (2:53%). Slow loris stable habituation never seen doing in-active behavior and abnormal during the observation took place. Keywords: Daily behavior, habituation cage, rehabilitation, slow loris.